Boundary uniqueness theorems for polyanalytic functions - Petrov, V. A. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Петров. Граничные теоремы единственности для полианалитических функций V. Petrovas. Kraštinės vienatinumo teoremos polianalizinių funkcijų atveju